Towards Teachers’ Communicative Competence Enhancement: A Study on School Preparation for Bilingual Programs - Heny Hartono; Mursid Saleh; Warsono Warsono; Dwi Anggani (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
This research is a preliminary study of an empirical research aimed to develop an English training model to enhance teachers’ communicative competence in bilingual schools. This preliminary study aims to give a description of the schools’ background and preparation to run bilingual programs, teachers’ background and experience in teaching using English, and the challenges related to communicative competence which are faced by teachers inside and outside the classrooms. This study was a qualitative study and the data were collected using semi-structured interview, open-ended questionnaire, and focus group discussion. This study involved 54 teachers and 5 school principals. The results of the study revealed that the schools under this study were under the category of additive bilingual education; the teachers in the bilingual programs were English and non-English Department graduates; and the challenges faced by the teachers were mostly related with their teaching experience and educational background. The findings of this study will be useful to recommend teacher trainings as a part of teachers’ professional development.